2022
DOI: 10.1155/2022/6202746
|View full text |Cite
|
Sign up to set email alerts
|

The Innovation and Development Path of Cultural and Creative Industries in Anhui Province, China: Nvivo12-Based Policy Text Analysis

Abstract: The policy planning of cultural and creative industries is the leading factor affecting the development of cultural and creative industries and is also an important factor in driving China’s economic transformation. How to combine the policy with the actual industrial development and how to scientifically assess the construction effect of cultural and creative industries and build the corresponding planning system are the key points of the current development of cultural and creative industries in Anhui Provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The study gathered qualitative data from six facets that are identified as "Themes". Zeng & Yang (2022) uses qualitive analysis to investigate the regional cultural characteristics and development status of Anhui Province firstly and makes in-depth analysis of 20 policy texts about Chinese cultural and creative industry development by performing grounded research and qualitative text analysis through the Nvivo12 qualitative analysis software. This study put forward three core elements, namely, development task, development goal and development guarantee, which may inspire policy makers for further innovation and development of cultural and creative industries in Anhui province.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study gathered qualitative data from six facets that are identified as "Themes". Zeng & Yang (2022) uses qualitive analysis to investigate the regional cultural characteristics and development status of Anhui Province firstly and makes in-depth analysis of 20 policy texts about Chinese cultural and creative industry development by performing grounded research and qualitative text analysis through the Nvivo12 qualitative analysis software. This study put forward three core elements, namely, development task, development goal and development guarantee, which may inspire policy makers for further innovation and development of cultural and creative industries in Anhui province.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a strong economic and cultural province in China, Anhui province is rich in cultural resources and has a high level of economic development, which provides unique conditions for the development of cultural industries (Zeng & Yang, 2022). As shown in Table 1, the valueadded of cultural and related industries in Anhui province grew from RMB 105.231 billion in 2016, to RMB 119.595 billion in 2017, and to RMB153.728 billion in 2018, occupying compositions of gross domestic product (GDP) 4.03%, 4.00% and 4.52% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Proses menjadi lebih cepat karena terbantu dalam proses transkrip hasil wawancara, terbantu dalam proses coding jawaban informan, terbantu dalam proses visualisasi jawaban informan, dan berbagai kemudahan lainnya (Dalkin et al 2021). Salah satu yang software yang user friendly dan sangat membantu proses penyelesaian riset kualitatif berbasis data hasil wawancara, yaitu software NVivo 12 Plus (Zeng and Yang 2022). Software NVivo ini banyak digunakan oleh para peneliti pemula maupun peneliti yang sudah berpengalaman (Soehardi et al 2021).…”
Section: Pendahuluanunclassified
“…Tong (2021) focuses on the foreign trade aspect of Beijing's cultural and creative industry, identifying the small scale and need for diversified patterns. Zeng (2022) analyses the development of cultural and creative industries in Anhui Province, emphasising the need for policy integration, regional characteristics, and structural optimisation. Li (2010) explores marketing strategies in the cultural and creative industry, using the Palace Museum as a case study and suggesting improvements in copyright protection and international promotion.…”
Section: Introductionmentioning
confidence: 99%